Understanding The Impact Of Manager’s Political Skills On Compassion Behavior Towards Colleges: A Glams From Banking Sector Of Pakistan - Dr. GhulamDastgeer,; Khalid, Afsheen (The journal of contemporary issues in business and government, 2021)
Among other social effectiveness constructs, political skill has attained more prominence in organizational psychology. The political skill helps the managers to cope up with workplace challenges and cultivating a healthy work environment.The study made an attempt to investigate the role of managers’ political skill in performing compassion behavior towards others with the mediating role of interpersonal trust.The data was gathered from the sample of 219 managers serving in banks of Pakistan. Political skill inventory scale, dispositional positive emotion subscale for compassion and interpersonal trust scale were used to measure the constructs.The results revealed a partial mediation of interpersonal trust using process macro. Political skill helps the management to develop trust in coworkers and being more efficient and vigilant in feeling, noticing and responding the pain of coworkers by showing a compassionate behavior. The politically skilled individuals can be placed in the positions where there is more of a social interaction hence providing an edge to excel and work for the betterment of organization and colleagues.